2020
DOI: 10.3389/fnut.2020.00134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing β-Carotene Concentration in Parental Lines of CO6 Maize Hybrid Through Marker-Assisted Backcross Breeding (MABB)

Abstract: Vitamin A deficiency (VAD) is a global health problem; many people around the world, especially children and pregnant women, are VAD deficient or insufficient. Maize is known as an important source of provitamin A for humans. Hence, enhancement of provitamin A carotenoids (pVAC) in maize varieties through breeding or biofortification is a good option for alleviating VAD in developing countries, especially India. So far, numerous maize hybrids have been developed in India. Among them, CO6, derived from UMI1200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…The high degree of resemblance with their recurrent parent for the trait of plant height in the present study agreed with earlier reports of Mehta et al [ 25 ] when developing sweet corn hybrids for vitamin A fortification. The high rate of recurrent parent recovery in the BC 2 F 2 generation was also reported in previous studies [ 8 , 9 , 11 , 26 ]. The improved line CAUM66-54-9-12-24 recorded high β-carotene (8.711 μg/g) comparable to that of the donor parent (UMI285β + ) followed by the lines, viz., CAUM66-54-9-12-13 and CAUM66-54-9-12-11 which recorded 8.647 μg/g and 8.258 μg/g, respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The high degree of resemblance with their recurrent parent for the trait of plant height in the present study agreed with earlier reports of Mehta et al [ 25 ] when developing sweet corn hybrids for vitamin A fortification. The high rate of recurrent parent recovery in the BC 2 F 2 generation was also reported in previous studies [ 8 , 9 , 11 , 26 ]. The improved line CAUM66-54-9-12-24 recorded high β-carotene (8.711 μg/g) comparable to that of the donor parent (UMI285β + ) followed by the lines, viz., CAUM66-54-9-12-13 and CAUM66-54-9-12-11 which recorded 8.647 μg/g and 8.258 μg/g, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…Hence, allele 1 is identified as a favorable allele that is responsible for the accumulation of a higher level of β-carotene in the maize endosperm. Many researchers used the gene-specific markers developed from the crtRB1 gene in MABC programs to increase the β-carotene content in popular elite varieties and hybrids [ 8 , 9 , 10 , 11 ]. In the NEHR of India, maize is the staple food crop and the local people cultivate the maize landraces and consume them as food.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al (2018) reported the increase of acticity around 7.7% using modified corn omso-coating substrate for β-Carotene (Song et al , 2018). Natesan et al , 2020 have reported a method of increasing the concentration of β -Carotene through Marker-Assisted Backcross Breeding in CO 6 Maize hybrid.…”
Section: Plackett–burman Designmentioning
confidence: 99%
“…Several studies in India and other parts of the world have successfully introgressed either crtRB1 or o2 into popular elite lines and improved the β-carotene, lysine, and tryptophan contents 24 30 . The common determinant in all the previous studies is the introgression of a single factor into an established variety.…”
Section: Introductionmentioning
confidence: 99%